ChemInform Abstract: C—C Bond Forming Reactions Catalyzed by Chiral Metalloporphyrins. Issue 37 (August 2016) - Rybicka‐Jasinska, Katarzyna; Ciszewski, Lukasz W.; Gryko, Daniel T.; Gryko, Dorota
Abstract: Review: 74 refs.